Адамів рід у фразеографічному висвітленні - Дядечко, Л.П.; Суховій, О. (Лексикографічний бюлетень, 2012)
The article presents a few dictionary entries for phraseological units with the constituent Адам / Адамів that denote humankind in the Russian-Ukrainian Dictionary of Biblical Phraseologisms. Russian-Ukrainian phraseography, thesaurus, a phraseologism of biblical origin.